Regional Competitiveness: In Search of a Framework for Greek Regions Strategic Planning and Measurement of Competitiveness - George Mihailidis; Giorgos Georgiadis; Nikos Koutsomarkos (European Regional Science Association (ERSA), 2006)
(This paper is the result of a research program that was carried out by the Laboratory for Evaluation of Development Policies and Programs, University of Thessaly). Greek economy, after nominal converging with other western European countries and meeting the accession criteria to the European Monetary Union, sets as a new objective the attainment of "real" convergence. Success in this objective, while operating in a globalized economic environment and the single European market, will be judged on the choice of a development policy focused on competitiveness and regional development. This paper exactly aims at informing the strategic planning of a regional competitiveness policy. Especially, it intends to set specifications for a regional competitiveness strategy, to define actions at an institutional level for its implementation and to propose a quantification and measurement system of its results. Based on the definition of competitiveness and its determinant factors for each level (national, branch, enterprise, regional) and how they are intertwined, the necessity for a regional competitiveness strategy is validated by a critical analysis of Greek economys recent related data and performance. The frame in which Greek regions competitiveness problems will be addressed is analyzed under the light of the European Unions new regional development policies Furthermore, the article analyzes the competitiveness strategic planning of Greece and Greek regions in interventions of the current programming period. Namely, it evaluates the extent at which competitiveness is identified and specified in the Community Support Programme, the Competitiveness Operational Programme and the SWOT analyses of the Regional Operational Programmes. Moreover the policies that implement the European regional policy (CSP, OP) and the competitiveness policy (COP) are being evaluated on aspects that include fund allocation, strategy update, regional priorities, implementation progress, efficiency, performance, and synergies, as far as competitiveness and its determinant factors are concerned. Based on literature review, the paper assesses and analyzes the most renowned benchmark systems of countries and regions competitiveness. This paper results to a coherent set of proposals for regional competitiveness policy strategic planning. Particularly, it defines requests towards the aforementioned policy and identifies important issues for the forthcoming programming period. It proposes the establishment of regional agencies analogous to the National Competitiveness and Development Council, alternative organizational forms and a typical action plan. It defines an index set for Greek regions competitiveness benchmarking, a synthesis and utilization methodology, and evaluates the documentation of available data.
Keywords: 330